BCL-xL Is a Target Gene Regulated by Hypoxia-inducible Factor-1α - Chen, Ni (American Society for Biochemistry and Molecular Biology, 2009)
The transcription factor hypoxia-inducible factor-1α (HIF-1α) plays pivotal roles in physiology and pathophysiology. Constitutive or hypoxia-induced HIF-1α overexpression is observed in many types of cancers including prostate adenocarcinoma, in which it is associated with resistance to apoptosis and therapeutic agents. BCL-xL, a hypoxia-responsive, anti-apoptotic protein of the Bcl-2 family, is also overexpressed in prostate carcinoma and many other cancers. Despite this connection, whether BCL-xL expression is directly regulated by HIF-1α is not known. We used prostate cancer PC-3 cell with constitutive high HIF-1α level as a model to address this important question. We first generated prostate cancer PC-3 cells in which HIF-1α was stably knocked-down (HIF-KD) by using small interference RNA. BCL-xL was dramatically decreased in HIF-KD PC-3 cells, in parallel with sensitization to apoptosis with caspase-3 activation as well as decreased cell proliferation. We then demonstrated that HIF-1α directly regulated BCL-xL transcription by binding to a hypoxia-responsive element in the BCL-xL promoter (-865 to -847) by reporter gene assay, chromatin immunoprecipitation, and electrophoretic mobility shift and supershift assays. HIF-1α-dependent BCL-xL overexpression may be an important mechanism by which HIF-1α protects prostate cancer cells from apoptosis and leads to treatment resistance.